задание СОЧ за 4 четверть. +(3x-1/3x-10)​

devil2a devil2a    3   20.05.2020 12:56    1

Ответы
Арсенал11 Арсенал11  15.10.2020 02:07

Объяснение:

(\frac{3}{2x-1}:\frac{3x-1}{4x^{2} -1} -\frac{6}{3x-1})*\frac{3}{2x-1} +(\frac{3x-10}{3x-1} )=\\ =(\frac{3}{2x-1}*\frac{(2x+1)*(2x-1)}{3x-1} -\frac{6}{3x-1})*\frac{3}{2x-1} +(\frac{3x-10}{3x-1} )=\\ =(\frac{3*(2x+1)*(2x-1)}{(2x-1)*(3x-1)} -\frac{6}{3x-1} )*\frac{3}{2x-1} + (\frac{3x-10}{3x-1} )=\\ =(\frac{6x+3}{3x-1} -\frac{6}{3x-1} )*\frac{3}{2x-1}+(\frac{3x-10}{3x-1} )= \frac{6x+3-6}{3x-1} *\frac{3}{2x-1} +(\frac{3x-10}{3x-1} )= \\

=\frac{6x-3}{3x-1}*\frac{3}{2x-1} + \frac{3x-10}{3x-1} =\frac{3*(2x-1)*3}{(3x-1)*(2x-1)} + \frac{3x-10}{3x-1} =\frac{9}{3x-1} +\frac{3x-10}{3x-1}=\\ =\frac{9+3x-10}{3x-1}=\frac{3x-1}{3x-1}=1.

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра